2018 31st SIBGRAPI Conference on Graphics, Patterns and Images (SIBGRAPI) 2018
DOI: 10.1109/sibgrapi.2018.00044
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Preprocessing on Deep Representations for Iris Recognition on Unconstrained Environments

Abstract: The use of iris as a biometric trait is widely used because of its high level of distinction and uniqueness. Nowadays, one of the major research challenges relies on the recognition of iris images obtained in visible spectrum under unconstrained environments. In this scenario, the acquired iris are affected by capture distance, rotation, blur, motion blur, low contrast and specular reflection, creating noises that disturb the iris recognition systems. Besides delineating the iris region, usually preprocessing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 47 publications
0
39
0
Order By: Relevance
“…Recently, machine learning techniques based on deep learning have been achieving great popularity due to the results reported in the literature, which advance the state-of-the-art in various problems such as speech recognition [8][9][10], natural language processing [11,12], digit and character recognition [13,14] and face recognition [15,16]. In the field of ocular biometrics, using deep learning representation has been advocated both for the periocular [17,18] and iris [6,[19][20][21][22][23][24][25] regions, with interesting and promising results being reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, machine learning techniques based on deep learning have been achieving great popularity due to the results reported in the literature, which advance the state-of-the-art in various problems such as speech recognition [8][9][10], natural language processing [11,12], digit and character recognition [13,14] and face recognition [15,16]. In the field of ocular biometrics, using deep learning representation has been advocated both for the periocular [17,18] and iris [6,[19][20][21][22][23][24][25] regions, with interesting and promising results being reported.…”
Section: Introductionmentioning
confidence: 99%
“…The strategy described in this paper is composed of some methodologies extracted from the literature. For both the iris and ocular traits, we use as input the bounding box delimited regions used in the state-of-the-art methods [17,25]. Then, the features from these traits were extracted using a similar approach proposed by Zanlorensi et al [25].…”
Section: Introductionmentioning
confidence: 99%
“…An overview of the important features of all databases used in this work can be seen in Table II. These databases were chosen because they are widely used in the biometric recognition literature [23], [27]- [29], which we plan to investigate in future works.…”
Section: A Databasesmentioning
confidence: 99%
“…Typically, in biometric systems that use iris and/or periocular region images as input, the first step in which efforts should be applied is the detection of the Region of Interest (ROI) [21], as a poor detection would probably impair the effectiveness of the subsequent steps of the system [12], [22]. Recently, Zanlorensi et al [23] showed that impressive iris recognition rates can be achieved when using deep representations having as system input the bounding boxes of the iris region, without the iris segmentation preprocessing. Also using deep representations and having as input a squared region (i.e., a bounding box), Luz et al [24] achieved state-of-the-art results for periocular recognition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation